Pengaruh Berbagai Media Tanam dan Konsentrasi Pupuk Organik Cair (POC) Urine Kelinci terhadap Pertumbuhan serta Hasil Tanaman Sawi Hijau (Brassica juncea L) - Setiyanto Setiyanto; Pramono Hadi; Srie Juli Rachmawatie (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study evaluated the effects of growing media and rabbit urine liquid organic fertilizer (LOF) concentrations on the growth and yield of mustard greens (Brassica juncea L.) in Klaten Regency, Indonesia. A factorial completely randomized design tested three growing media (cow, goat, and chicken manure mixed with fermented rice husk at a 1:1 ratio) and three LOF concentrations (10, 20, and 30 mL L⁻¹). Plant height, leaf number, fresh weight, and root weight were measured and analyzed using ANOVA followed by Duncan’s multiple range test (α = 0.05). Growing media had no significant effect on any parameter. LOF concentration significantly increased leaf number but did not affect plant height, fresh weight, or root weight, and no interaction effects were detected. These results indicate that rabbit urine LOF primarily promotes vegetative leaf development rather than overall biomass accumulation in mustard greens.